Application of coupled CFD-DEM modelling in erosion study of cohesive materials: A case study of rotating finger test - Mohsen Rahimi-Larki; Burhanuddin; Sandra Vollmann; Shengli Jin; Harald Harmuth (Results in Engineering)
The Erosion of cohesive materials due to fluid-induced shear stress at the liquid-solid interface is a continuous wear mechanism. The erosion resistance of cohesive materials is largely influenced by the strength of the bonds between particles, which adds complexity to the erosion process. The erosion rate of cohesive materials depends on their critical shear stress and erodibility coefficient. The relationships among the cohesiveness, critical shear stress (CSS), and erodibility coefficient and their contributions to the flow-induced erosion process have not yet been extensively investigated. This study introduces a coupled computational fluid dynamics (CFD) and discrete element method (DEM) approach to quantitatively assess the flow-induced erosion of cohesive materials. A cohesion model was used to describe the cohesive behaviour of the materials, and the relation between cohesion energy density (CED), friction coefficient, critical shear stress, and erodibility coefficient were investigated. The results indicated that the CED and friction coefficient are the key factors that significantly influence the erosion parameters of cohesive materials. A method for erosion rate determination based on the CFD-DEM simulation results is established. The method was successfully applied to rotating finger test (RFT) experiment to evaluate the erosion rate. The capability and accuracy of method were examined by comparing the obtained results with experimental data. This study lays the foundation for future research aimed at deepening the understanding of cohesive material erosion and promoting its quantification in different applications and geometries.